Monitoring of a biodiesel production process via reset observer. (June 2016) - Aguilar-Garnica, Efrén; García-Sandoval, Juan Paulo; Dochain, Denis
Abstract : Highlights: A biodiesel production process has been monitored with a couple of fuzzy observers. This process is an esterification of Free Fatty Acids (FFAs) from grease trap wastes. The observers estimate the concentration of FFAs from temperature's measurements. The observers are derived from a fuzzy representation of the esterification's model. The reset observer performs the estimation better than the classical observer. Abstract: This paper is concerned with the monitoring of a biodiesel production process, more specifically with the monitoring of the esterification of grease trap wastes, a low quality feedstock for biodiesel production typically characterized by its high content of Free Fatty Acids (FFAs). The esterification takes place in a jacketed Continuous Stirred Tank Reactor (CSTR). A reset observer is designed and applied in order to provide on-line estimation of the concentration of FFAs from temperature measurements within the CSTR. In addition, the proposed reset observer is compared to two other observers (classical fuzzy observer and extended Kalman filter). According to a multiple range test conducted for analyzing the estimation error, the monitoring task for the process under study has been better fulfilled by the reset observer which is able to update the estimation results every instant when the measurements were available.